Einleitung zum Thementeil 2: Reformation als Herausforderung für die Bildungslandschaft heute". Dokumentation der Ringvorlesung im Jubiläumsjahr der Universität Wien und im Jahr der Bildung der Evangelischen Kirche in Österreich - Rothgangel, Martin (Theo-Web, 2016)
'Reformation as challenge for today's educational landscape' was the title of a lecture series that took place at Vienna University in the summer semester of 2015. It marked the double occasion of the 650th anniversary of Vienna University on the one hand and of the Year of Education of the Protestant Church of Austria on the other hand. It was conducted by the following cooperating actors: the Vienna University (Faculty of Protestant Theology, Faculty of Philosophy and Educational Science, Faculty of Catholic Theology, Centre for Teacher Education), the The University College of Teacher Education Vienna/Krems (KPH) and the Protestant Church of Austria. (English)